(untitled) (American Journal of Islam and Society, 2001)
This book, originally published in 1962, has now become a classic on the history of modemTurkish political thought, whose beginning is usually traced back to the T-t period (1836-1878), the most turbulent and crucial period of modem Turkish history. Serif Mardin, the famous Turkish historian and political scientist, is like a household name to those interested in modern Ottoman and Turkish intellectual history. In his numerous books and articles, which followed the publication of the present work, Mardin took the herculean task of unearthing the parameters of modem Turkish thought with an almost solitary conscience. It is simply impossible to have a discussion about Islam and Turkish society, social change, modernization or secularization without referring to Mardin’s work, which is woven around a string of ideas, concepts and analytical tools, all of which enable him to see the realities of Turkey and the modem Islamic world both from within and from without. His more recent Relwon and Social change in Twkey: ’ c irhe of&aYuzaman Said Nuni (New York: SUNY Press, 1989),w hich is the single most important book written in English on Said Nursi, the founder of the Nurcu movement in Turkey, is the result of the same set of principles Mardin has adopted throughout his career: diligent scholarship, resistance to fads, and willingness to understand before passing any judgements on his subject. The present work under review touches upon the most sensitive and crucial period of modem Turkish history, viz., the end of the Ottoman era and the establishment of the modem Turkish Republic. Mardin’s exclusive emphasis is on the Tanzirnat period, and the figures that laid the intellectual foundations of it. The significance of this period can hardly be overemphasized, not only for Turkish history but also for the rest of the Islamic world. It was in this period that a whole generation of ottoman intellectuals, from right to left, was faced with the historic task of confronting modem western civilization in the profoundest sense of the term, and their successes and failures set the agenda for the modem intellectual history of Turkey for decades to follow. Their troublesome journey was shaped by the historical setting, in which they came to terms with such questions as modernism, secularism, westernization, nationalism, Islam, society, science, tradition, and a host of other issues that continue to haunt the minds of the Islamic world today. Their trial, however, was linked to the rest of the members of the Islamic world in ways, as the present work under review shows, more important than is usually thought, and this issue, namely the place of ottoman intellectual history within the larger context of modem klamic thought, has not been resolved. In this ...